Entrepreneur Characteristics, Human Capital Diversity and Access to Debt Financing Among SMEs: Moderating Effect of Academic Qualification and Social Networks - Kwaning, Collins Owusu; Aidoo, Getrude Sarah; Tenobi , Deborah Emefa; Owusu, Ackah; Afriyie, Emelia Ohene (Journal of Ecohumanism, 2024)
The purpose of the study was to investigate entrepreneur characteristics and human capital diversity as determinants of debt financing among micro, small, and medium enterprises. Additionally, the moderating effect of academic qualification and social networks is ascertained. Drawing on a diverse sample from various micro, small and medium enterprises in Ghana, the research employs a cross-sectional quantitative survey design. The findings reveal significant positive relationships between entrepreneurial characteristics, human capital diversity, and access to debt financing. Additionally, academic qualifications demonstrate an interactive effect, enhancing the joint impact of entrepreneurial characteristics and human capital diversity on financial access. Social networks emerge as influential moderators, accentuating the importance of external relationships in shaping access to debt financing for entrepreneurs. The study contributes to a nuanced understanding of the factors influencing SMEs' financial outcomes and offers actionable insights for entrepreneurs, policymakers, and financial institutions.